What remains of Law No. 164/1982? Rights and sources of gender transition (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The article examines the meaning of the right to self-determination of gender identity. The constitutional jurisprudence that has developed regarding the application of Law No. 164/1982 has progressively softened its rigid regulatory framework, excluding the requirement of surgical conformity of primary sexual characteristics. Recently, with ruling No. 143/2024, the Constitutional Court has limited the judicial authorization for the execution of surgery. However, case law highlights new issues and protection requests (the condition of patients undergoing transition, the preservation of reproductive capacity, or the authorization of gender therapy for minors), which call for an update of sector-specific regulations, pushing towards a reconsideration of the judiciary’s functions.
Keywords: Gender-affirming care; health; fundamental rights; civil procedure; National Health Service